1998
DOI: 10.1385/endo:8:3:241
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Lipopolysaccharide on Tumor Necrosis Factor and Prolactin Release from Rat Anterior Pituitary Cells

Abstract: TNF-alpha plays a critical role in the cascade of neuroendocrine events during inflammation and septic shock. It also affects the release of pituitary hormones and acts as a growth factor in immune and nonimmune cells. The aim of the present study was to investigate the release of TNF-alpha from rat anterior pituitary cells and the effect of the steroid medium on its release. Cultured anterior pituitary cells from lactating rats spontaneously released TNF-alpha. The presence of lipopolysaccharide (LPS, 0.1 mic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
33
0

Year Published

2001
2001
2016
2016

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 35 publications
(33 citation statements)
references
References 31 publications
0
33
0
Order By: Relevance
“…TNF-␣ plays a central role during endotoxemia, initiating a cascade of synthesis of other factors required for an appropriate neuroendocrine response to infection (14). TNF-␣ is expressed in the pituitary gland after LPS administration (30) and is released from anterior pituitary cells in response to LPS (25). Since the anterior pituitary gland expresses TNF-␣ receptors (31) and this cytokine induces apoptosis of anterior pituitary cells (2), circulating and/or locally produced TNF-␣ could be involved in the apoptotic response of the anterior pituitary to endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…TNF-␣ plays a central role during endotoxemia, initiating a cascade of synthesis of other factors required for an appropriate neuroendocrine response to infection (14). TNF-␣ is expressed in the pituitary gland after LPS administration (30) and is released from anterior pituitary cells in response to LPS (25). Since the anterior pituitary gland expresses TNF-␣ receptors (31) and this cytokine induces apoptosis of anterior pituitary cells (2), circulating and/or locally produced TNF-␣ could be involved in the apoptotic response of the anterior pituitary to endotoxemia.…”
Section: Discussionmentioning
confidence: 99%
“…This sexual difference is abolished by gonadectomy and restored by administration of estradiol to ovariectomized (OVX) rats (28). We have observed that estradiol stimulates basal and LPS-induced TNF-␣ secretion from anterior pituitary cells of OVX rats (25). Also, TNF-␣ release from anterior pituitary cells varies along the estrous cycle reaching the highest levels in cells from rats at proestrus (26).…”
Section: Lipopolysaccharide (Lps)mentioning
confidence: 99%
See 1 more Smart Citation
“…This cytokine is synthesized and released by anterior pituitary cells [2, 3, 4]. TNF-α binding sites have been detected in the rat anterior pituitary with a K d similar to that calculated for human and mouse TNF-α receptor (TNFR) 1 [5].…”
Section: Introductionmentioning
confidence: 99%
“…TNF-α induces apoptosis in somatotrophs and, in an estrogen-dependent manner, mammotrophs (Candolfi et al, 2002). It also decreases PRL release (Theas et al, 1998). TNF-α release from pituitary glands was higher during proestrus (Theas et al, 2000), thus TNF-α inhibits PRL secretion and mammotroph growth.…”
Section: Calcitoninmentioning
confidence: 93%